Peran KJA Ary Wicaksono dalam Mengoptimalkan Proses Rekapitulasi PPh 21 PT XYZ - Boyani, Angelika Karonavita; Fitriani, Nurul (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study aims to analyze the role of the Accounting Services Office (KJA) Ary Wicaksono in optimizing the recapitulation process of Income Tax (PPh) Article 21 at PT XYZ and identify the factors causing recording errors that lead to discrepancies between tax reports and the company's financial statements. This study uses a case study approach with a qualitative descriptive method, which collects data through in-depth interviews, direct observation, and related documentation. The results of the study indicate that recording errors mainly occur due to human error, such as inaccuracy in data input and negligence in entering the latest corrections into the PPh 21 Periodic Tax Return (SPT). KJA Ary Wicaksono actively provides assistance through systematic recapitulation procedures, recording consultations, and education to PT XYZ staff to ensure all data and recording. The findings of this study reinforce the importance of the involvement of external accounting professionals in managing tax obligations effectively, supporting the consistency of tax and accounting reporting, and increasing the company's credibility and reputation in the eyes of tax authorities and other stakeholders in a sustainable manner.